EFFECT OF URETHRAL DILATION ON ANTERIOR URETHRAL STRICTURE RECURRENCE AFTER INTERNAL URETHROTOMY IN MALES - Hapsari, Edhi; Hamid, Agus Rizal AH; Rodjani, Arry; Firdaoessaleh, Firdaoessaleh; HR, Danarto (Indonesian Journal of Urology, 2013)
Objective: The aim is to evaluate the effect of urethral dilation on anterior urethral stricture recurrences after direct vision internal urethrotomy (DVIU). Material & Method: Patients were classified into 2 groups after internal urethrotomy for urethral dilation or observation. All strictures included were anterior, single, and causing partial obstruction. Urethral dilation was performed using a metal sound. This procedure was performed every 1 or 2 weeks in the first and second month after operation and then once a month for 1 year or in case of voiding complaints or low flow rate (< 10 mL/s). Follow up at least until 1 year after DVIU. Results: A total of 32 cases could be reviewed, of which are 21 had urethral dilation and 11 observation only. In the urethral dilation group, we found 4 recurrences (19%) with mean time to recurrence 10,52 months. In the observation group, we found 7 recurrent cases (63,63%) with a mean time to recurrence of 8,09 months. P value is 0,02 which means urethral dilation significantly decreased the chance of stricture recurrence. By Kaplan Meier survival analysis, urethral dilation had a better and longer time to recurrence. Conclusion: In this study, regular meatal dilation is proven to prolong the time to recurrence of an anterior urethral stricture after DVIU. Keywords: Urethral dilation, anterior urethral stricture, stricture recurrence.